Halal Certification Obligations for Hamper-Based Florist Businesses in Indonesia: A Juridical and Islamic Economic Law Perspective - Nasrudin Nasrudin; Muharrik Fitragara Fachreza (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
The development of hamper-based florist businesses in Indonesia indicates a shift in business models from decorative services to the distribution of consumamble products, which has legal implications, particularly regarding halal certification obligations. This study aims to analyze halal certification obligations for hamper-based florist businesses from the perspectives of positive law and Islamic economic law. This study employs a normative juridical methodology with legislative, conceptual, and analytical approaches. The data utilized consists of primary, secondary, and tertiary legal sources obtained through literature review and analyzed qualitatively using deductive reasoning. The results of the study indicate that the halal certification obligations for hamper-based florist businesses is conditional, depending on the level of the business operator’s involvement in the production, repackaging, and distribution of consumamble products. Florists engaged solely in decorative services are not subject to such obligations, whereas florists involved in the production or repackaging of consumable products face a stronger juridical obligations. From the perspective of Islamic economic law, this obligation has a broader scope, as it takes into account the principles of halalan tayyiban, the prohibition of gharar, and the concept of maslahah. These three principles require clarity, safety, and benefit for consumers, so florist hamper businesses are required to exercise greater caution in ensuring the halal status of the products they trade.